A comparative study of risk disclosures in the banking sector in China and UK - Cai, Xuanyan (2011)
Driven in large part by the recent financial crisis and the advancement of accounting standards, the notion of risk disclosures particularly in the banking sector has received increasing attention. Focusing on the risks of financial instruments (i.e. credit, liquidity and market risk), this study provides insights on the risk disclosure patterns of a sample of UK and Chinese banks for the examined year 2006 and 2010 following the adoption of the IFRS 7 (International Financial Reporting Standard). Using the content analysis, new index frameworks examining the quantity as well as the quality of risk disclosures are constructed and applied to the annual reports of banks. The findings reveal that the disclosure levels have increased significantly over time and there does not always appear to be a consistency in quantity and quality disclosures. Moreover, UK is found to be more advanced than China concerning the quantity of risk reporting but not in the quality case, and the disclosure level is not positively associated with bank size which is opposed to most prior results.